O fórum de educação infantil da Paraíba e sua articulação com as políticas educacionais - Vasconcelos, Thais Gomes de (2021)
The Child Education Forums are social movements that are active in debates and formulation of public policy for children from zero to six years of age in Brazil. Knowing their political articulations is of utmost importance for educational policy, due to their activities in all Brazilian states and in the Federal District and due to the influence they exert in the Brazilian educational context, considering the achievement of rights to basic education and the guarantee of its funding, especially for early childhood. In view of this, this dissertation has as its general objective to analyze the articulation of the Early Childhood Education Forum of the State of Paraíba (FEIPB), in relation to state and national educational policies. The research was guided by the following specific objectives: to map the educational policies for young children since the 1988 Federal Constitution; to know what the Early Childhood Education forums are and how they act; and to historicize the creation and performance of FEIPB. As a theoretical reference, the analyses were based on the sociological perspective of Lascoumes and Le Galés (2012) and the Policy Cycle proposed by Stephen Ball (2009, 2014, 2015), which consists of five articulated contexts to understand educational policies: context of influence, context of text production, context of practice, context of result, and context of strategy. This choice was made because this analytical model allows us to understand the different phases of educational policy formulation and implementation. This is a qualitative research that unfolds from documentary and bibliographic analyses, and semi-structured interviews with key informants. Finally, it was identified during the research that the conquest of children's rights involved several subjects among them the social movements, such as the Paraíba Early Childhood Education Forum. In the analysis of the empirical material, from the categories: historical memory of the FEIPB; pandemic; and political subject, it was realized that, despite a fragmented history and with few and sparse records, its performance at the national level and in the State of Paraíba is noteworthy.